Rapid RNase inhibitor production to enable low‐cost, on‐demand cell‐free protein synthesis biosensor use in human body fluids. Issue 10 (23rd July 2021) - Soltani, Mehran; Hunt, J. Porter; Bundy, Bradley C.
Abstract: Human body fluids contain biomarkers which are used extensively for prognostication, diagnosis, monitoring, and evaluation of different treatments for a variety of diseases and disorders. The application of biosensors based on cell‐free protein synthesis (CFPS) offers numerous advantages including on‐demand and at‐home use for fast, accurate detection of a variety of biomarkers in human fluids at an affordable price. However, current CFPS‐based biosensors use commercial RNase inhibitors to inhibit different RNases present in human fluids and this reagent is approximately 90% of the expense of these biosensors. Here the flexible nature of Escherichia coli ‐lysate‐based CFPS was used for the first time to produce murine RNase Inhibitor (m‐RI) and to optimize its soluble and active production by tuning reaction temperature, reaction time, reduced potential, and addition of GroEL/ES folding chaperons. Furthermore, RNase inhibition activity of m‐RI with the highest activity and stability was determined against increasing amounts of three human fluids of serum, saliva, and urine (0%–100% v/v) in lyophilized CFPS reactions. To further demonstrate the utility of the CFPS‐produced m‐RI, a lyophilized saliva‐based glutamine biosensor was demonstrated to effectively work with saliva samples. Overall, the use of CFPS‐produced m‐RI reduces the total reagent costs of CFPS‐based biosensors used in human body fluids approximately 90%. Abstract : Schematic illustration of Cell‐Free Protein Synthesis (CFPS) biosensors compatible with human body fluids. Soluble murine RNase Inhibitor (m‐RI) was produced in the first CFPS reaction and then added to the second CFPS reaction to protect target protein expression against RNases present in human body fluids.